2017
DOI: 10.1186/s12889-017-4187-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring community participation in project design: application of the community conversation approach to improve maternal and newborn health in Zambia

Abstract: BackgroundThe United Nations Development Programme (UNDP) has adopted an approach entitled Community Conversation (CC) to improve community engagement in addressing health challenges. CCs are based on Paulo Freire’s transformative communication approach, in which communities pose problems and critically examine their everyday life experiences through discussion. We adopted this approach to engage communities in maternal and newborn health discussions in three rural districts of Zambia, with the aim of developi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…In sub-Saharan Africa, the barriers to access and uptake of maternal-child health services include geographical and financial inaccessibility, poorly equipped facilities, unaffordable user fees, and clients’ perceptions or experiences of healthcare worker incompetence and/or unprofessional attitudes [ 15 – 20 ]. Socio-cultural factors relating to the traditional, expected roles of women in African societies also underlie many of these barriers [ 4 , 17 , 21 23 ]. In some of these settings, women are unable to independently make health-related decisions for themselves [ 9 , 24 ], due to patriarchal norms [ 3 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In sub-Saharan Africa, the barriers to access and uptake of maternal-child health services include geographical and financial inaccessibility, poorly equipped facilities, unaffordable user fees, and clients’ perceptions or experiences of healthcare worker incompetence and/or unprofessional attitudes [ 15 – 20 ]. Socio-cultural factors relating to the traditional, expected roles of women in African societies also underlie many of these barriers [ 4 , 17 , 21 23 ]. In some of these settings, women are unable to independently make health-related decisions for themselves [ 9 , 24 ], due to patriarchal norms [ 3 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the participants reported that dialogue between the community and health providers would help identify obstacles affecting the use of FP/C services, and allow for the joint development of locally relevant implementable solutions. Other studies have used community dialogues in identifying and implementing context-relevant interventions to improve maternal and child health outcomes [26]. Furthermore, community dialogues can facilitate participation in health services by providing a platform for the health system to engage community actors such as parents and religious leaders who are vital in generating wider community support FP/C services [27].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the participants reported that dialogue between the community and health providers would help identify obstacles affecting the use of FP/C services, and allow for the joint development of locally relevant implementable solutions. Other studies have used community dialogues in identifying and implementing context relevant interventions to improve maternal and child health outcomes [26]. Furthermore, community dialogues have been shown to play an important role in facilitating participation in health services as they provide a platform for the health system to engage community actors such as parents and religious leaders who are vital in generating wider community support FP/C services [27].…”
Section: Discussionmentioning
confidence: 99%